Effects of Auditory Enrichment on Welfare and Performance of Sows During Pregnancy and Farrowing/lactation Periods - de Castro Lippi, Isabela Cristina [UNESP]; Caldara, Fabiana Ribeiro; Morais, Henrique Biasotto; Vargas, Larissa Braganholo; Odakura, Agnês Markiy; de Castro Burbarelli, Maria Fernanda; Felix, Gisele Aparecida; Garcia, Rodrigo Garófallo; Almeida Paz, Ibiara Correia Lima [UNESP]; dos Santos, Luan Sousa (Taylor & Francis, 2023)
This study is an observational study that aimed to evaluate whether exposure to music in the final third of sows’ gestation and during farrowing/lactation would change behavior, reduce stress, and improve reproductive rates. Forty-eight sows were used at 90 days of gestation until the weaning of their piglets. During gestation, sows were divided into two treatments: control and with music enrichment. In farrowing/lactation, sows were divided into four treatments: control–control (without music); control–music (music during farrowing/lactation); music–control (music during pregnancy); music–music (music in both phases). Sows’ behavior, eye temperature, and reproductive performance were evaluated. In the gestation phase, control group sows remained standing more times and had more negative interactions with the other sows in the pen. In the farrowing/lactating phase, sows exposed to music presented more nursing behaviors. The number of weaned piglets was higher in litters in which the sows had environmental enrichment in at least one of the phases of reproductive lives. Music may be used as environmental enrichment for sows in their reproductive phases due to beneficial responses in behavior, stress relief, and reproductive rates.
Keywords: Behavior; environmental enrichment; reproductive performance; stress reduction; welfare